Analisis Kepuasan Mahasiswa dalam Menggunakan Sistem Informasi Terpadu Akademik (SITA) Universitas Batanghari Jambi - Osrita Hapsara; Gupron Gupron; Andri Yandi (J-MAS (Jurnal Manajemen dan Sains), 2020)
This study aims to analyze the effect of system quality, information quality, and service quality on student satisfaction in using the Integrated Academic Information System (SITA) at Batanghari University (Unbari) Jambi. This research was conducted in the Unbari Jambi environment, with the population in this study were students in the Unbari Jambi environment. The sample in the study was 98 students with proportionate random sampling technique. Types and sources of research data consist of primary data, namely data obtained from the opinions of respondents through a research questionnaire, and secondary data, namely data obtained from Unbari Jambi. The data analysis technique used in testing the research hypothesis was multiple linear regression analysis using SPSS version 21.0 for windows. The results of the study found that: 1) system quality has a positive and significant effect on student satisfaction in Unbari Jambi; 2) the quality of information has a significant positive effect on student satisfaction in Unbari Jambi; 3) service quality has a significant positive effect on student satisfaction in Unbari Jambi; and 4) system quality, information quality, and service quality together have a significant effect on the satisfaction of Unbari Jambi students with a contribution of influence of 68.1% and the remaining 31.9% is influenced by other factors not included in the scope of this study.